The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1074/jbc.m116.749069
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of UDP-apiose Synthases from Bryophytes and Green Algae Provides Insight into the Appearance of Apiose-containing Glycans during Plant Evolution

Abstract: Apiose is a branched monosaccharide that is present in the cell wall pectic polysaccharides rhamnogalacturonan II and apiogalacturonan and in numerous plant secondary metabolites. These apiose-containing glycans are synthesized using UDPapiose as the donor. UDP-apiose (UDP-Api) together with UDPxylose is formed from UDP-glucuronic acid (UDP-GlcA) by UDP-Api synthase (UAS). It was hypothesized that the ability to form Api distinguishes vascular plants from the avascular plants and green algae. UAS from several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…Real time 1 H NMR spectroscopic analysis of the products formed when GrUAS reacts with UDP-GlcA ( Fig 6 and S1 Table ) confirmed that UDP-Api is the first product formed. GrUAS produces UDP-Api and UDP-Xyl in a ratio of ~1.7: 1.0, which is similar to characterized plant UASs [ 29 31 ]. The NMR study with GrUAS also confirmed that some of the UDP-Api is degraded and converted to the apiofuranosyl-1,2-cyclic phosphate during the in vitro reaction ( Fig 6 ); this instability of UDP-apiose is a known phenomenon [ 29 , 31 , 32 ].…”
Section: Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…Real time 1 H NMR spectroscopic analysis of the products formed when GrUAS reacts with UDP-GlcA ( Fig 6 and S1 Table ) confirmed that UDP-Api is the first product formed. GrUAS produces UDP-Api and UDP-Xyl in a ratio of ~1.7: 1.0, which is similar to characterized plant UASs [ 29 31 ]. The NMR study with GrUAS also confirmed that some of the UDP-Api is degraded and converted to the apiofuranosyl-1,2-cyclic phosphate during the in vitro reaction ( Fig 6 ); this instability of UDP-apiose is a known phenomenon [ 29 , 31 , 32 ].…”
Section: Resultssupporting
confidence: 57%
“…The recombinant GrUAS is most active in 50 mM Tris-HCl, pH 8.0–8.5, at 37°C ( Fig 7A and 7B ) and exists in solution as a dimer with a predicted size of 84 kDa ( Fig 7C ). Table 1 shows that GrUAS has a Km of 251 μM similar to that for Spirodela UAS [ 31 ], and a Kcat/ Km of 60.2 nM s -1 , while recombinant Arabidopsis AXS/UAS1 has a reported Km of 7 μM and Kcat/ Km of 43 nM s -1 [ 30 ]. Previous studies have shown that UAS is inhibited by certain nucleotides and nucleotide sugars, especially UDP-Xyl and UDP-GalA [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations